Sigmodontine community and species responses to El Niño and precipitation in different levels of forest degradation - Owen, Robert; Camp, Jeremy V.; Jonsson, Colleen B. (THERYA, 2019)
Few studies have focused on rodent communities at the margins of an ecoregion or the limits of speciesâ€™ distributions, where the community may be more sensitive to extrinsic variables, both biotic and abiotic. This study evaluates sigmodontine rodent species diversity and overall abundance, and variation associated with climatic variables, in three locations with differing levels of habitat degradation. The study was conducted in northeastern Paraguay, near the western limit of the Upper Paraná Atlantic Forest and near the distributional limits of the three most abundant species in the study sites. Three mark-recapture grids were established and classified as least, moderately and most-degraded based on an analysis of several vegetation parameters. The grids were sampled for five consecutive nights, six times during two years. Shannon diversity and overall abundance were calculated for each sample. Monthly Multivariate ENSO Index and rainfall values were obtained from publicly available resources. Product-moment correlations were calculated between community and climatic parameters, including cumulative values for the climatic variables. The same correlations were calculated for the three common sigmodontine species. 1,632 captures were recorded, representing 13 sigmodontine species. Species richness in the samples (one session on one grid) varied from four to seven. Akodon montensis, Hylaeamys megacephalus and Oligoryzomys nigripes were the three most abundant species. In general, species diversity was negatively correlated with ENSO index, precipitation and precipitation anomaly, including cumulative one- to six-month cumulative values of each. Total sigmodontine abundance was positively correlated with the climatic variables. However, these correlations were not uniform among the three levels of habitat degradation, nor did the three abundant species show similar correlation patterns. The three most abundant species are each near their distributional limits, whereas several less abundant species have distributions that extend well beyond the study area. This somewhat counterintuitive result bears further investigation in other sites at ecoregional margins, to determine whether it is a commonly observed pattern, or an exception. Overall sigmodontine abundances were generally reflective of Akodon montensis abundance, which generally correlated with precipitation (including cumulative amounts). Our analyses of these longitudinal data showed two major effects on sigmodontine species diversity and population. First, they are impacted by habitat and secondly, they are affected by climate (ENSO, precipitation). However, individual species are not impacted similarly. Akodon montensis abundances primarily were correlated with abiotic (climatic) variables, and the correlations were consistent across habitats (biotic factors). In contrast, Hylaeamys megacephalus abundance was correlated with climatic variables in two habitats, but not the moderately-degraded habitat, and Oligoryzomys nigripes abundance was not correlated with climate in the most-degraded habitat.